PENGEMBANGAN KONTEN PEMBELAJARAN ADMINISTRASI PERKANTORAN BERBASIS MEDIA TIKTOK PADA SISWA DI SMK - Wungow, Oktavia J. A.; Wantah, Edwin; Rooroh, Agnes; Wuisang, Jerry Rommy Herter (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2025)
ABSTRACT Students’ learning interest in office administration subjects at SMK Negeri 1 Tatapaan remains low due to the predominantly conventional delivery of the material. The use of social media platforms such as TikTok, which are highly popular among teenagers, is expected to serve as an effective tool to enhance student engagement and understanding of the subject matter. This study aims to develop TikTok-based instructional content for office administration as an innovation in the learning process. The research employed a Research and Development (R&D) approach using the 4-D model, consisting of Define, Design, Develop, and Disseminate. The participants were twelfth-grade students of the Office Administration Department, and data were collected using student needs questionnaires, expert validation sheets for material and media, and limited trials. The results indicate that the developed TikTok-based learning content for office administration is highly feasible in terms of material quality and media presentation, and it received very positive responses from students. Therefore, TikTok can be used as an innovative alternative medium for delivering office administration material in a more engaging, interactive manner that aligns with the characteristics of digital-generation learners. ABSTRAK Minat belajar siswa terhadap materi administrasi perkantoran di SMK Negeri 1 Tatapaan masih rendah karena kesesuaian materi yang cenderung konvensional. Penggunaan media sosial seperti TikTok yang populer di kalangan remaja diharapkan dapat menjadi sarana efektif untuk meningkatkan keterlibatan dan pemahaman siswa. Penelitian ini bertujuan untuk mengembangkan konten pembelajaran administrasi perkantoran berbasis media TikTok sebagai inovasi dalam proses pembelajaran. Metode penelitian menggunakan pendekatan Research and Development (R&D) dengan model pengembangan 4-D yang meliputi Define, Design, Develop, dan Disseminate. Subjek penelitian adalah siswa kelas XII Jurusan Administrasi Perkantoran, dengan instrumen berupa angket kebutuhan siswa, validasi ahli materi dan media, serta uji coba terbatas. Hasil penelitian menunjukkan bahwa konten pembelajaran administrasi perkantoran berbasis TikTok yang dikembangkan tergolong sangat layak dari segi isi materi dan media penyajian, serta mendapatkan respon yang sangat positif dari siswa. Oleh karena itu, media TikTok dapat menciptakan alternatif inovatif untuk menyampaikan materi administrasi perkantoran secara lebih menarik, interaktif, dan sesuai dengan karakteristik siswa generasi digital.